NUSYUZ AND ITS SOLUTIONS IN COMPILATION OF ISLAMIC LAW FROM THE PERSPECTIVE OF THE AL-QURAN - Ibnu Izzah (IAIN Bone, 2021)
Nusyuz and its solutions in Compilation of Islamic Law from the Perspective of the Al Quran is the title of this paper. Here the writer intends to find out how nusyuz and its solutions are reflected in the Compilation of Islamic Law (KHI). This study aims to: 1) describe and analyze settling nusyuz and its solution in the Islamic Law Compilation, and 2) suggesting the Quran perspective on nusyuz and its solution in the Islamic Law Compilation. The authors use two approaches in answering these problems: the normative theological approach and the formal juridical approach. This research is classified as a research library; data was collected by quoting, adapting, and analyzing using content analysis of representative literature and having relevance to the issues discussed, then reviewing and concluding.After discussing nusyuz and its solutions in KHI from the perspective of the Quran, we need to know that Nuyuz deeds are not only directed at one's wife but can also be punished by the husband based on the texts of the Quran, the views of some scholars and empirical facts that happened. Moreover, the Al-Quran solution has given to handle nusyuz wives with three stages: advice, separation of beds, and beatings so systematically, and when carried out according to the hierarchy, it is likely to make the family whole again and more harmonious. This can be actualized and become an alternative solution to the wife's nusyuz if we reflect on the conditions and problems that are dynamic in household conflicts today.